Challenges facing school principals in the implementation of the National Curriculum Statement in Capricorn District of the Limpopo Province - Magongoa, Malose Charles (My University, 2011)
The key aim of the study was to investigate whether school libraries in the rural schools of Nkangala region, Mpumalanga do implement budgeting policies due to funding constraints and poor service delivery. The library-computer centre can enhance teaching and learning. Some 188 school libraries were selected to explore their budgeting procedures and only 81 responded. The survey data collection method was used through a self-administered questionnaire which was distributed to teacher-librarians. The results of the study were analyzed according to frequencies and graphically displayed in table form. The results of the study show that almost all rural school libraries in the area have neither budgeting policies nor adequate budget to spend for effective service delivery. This shows that not only do school libraries experience budgetary constraints, but there might be other factors contributing to their poor library service delivery. It is important to empower school principals, SGBs and top managers in library budgeting procedures and for all to work cooperatively to achieve the expected educational goals.
Thesis (M.Ed. (Curriculum Studies)) --University of Limpopo, 2011
Keywords: School libraries policy implementation; School libraries budgets; Rural school libraries; School resource centres; 371.2012; School library finance